34.1: Novel Super‐Fast‐Response, Ultra‐Wide Temperature Range VA‐LCD. Issue 1 (1st July 2013) - Iwata, Yosuke; Murata, Mitsuhiro; Tanaka, Kohei; Jinda, Akihito; Ohtake, Tadashi; Shinomiya, Tokihiko; Yoshida, Hidefumi
Abstract: We have developed a novel super‐fast response (SFR) TFT‐LCD with an ultra‐wide temperature range. Both the turn‐on and turn‐off switching are forcibly controlled by applying an electric field. Response times of the SFR TFT‐LCD are over several times faster than those of conventional LCDs like MVA or IPS LCDs.